Mandibular Carcinoma Cuniculatum around the Dental Implant in a Patient with Concurrent Management for Pemphigus Vulgaris: A Case Report - Chika Murai; Ken-ichiro Sakata; Chisato Ouchi; Masanao Sonobe; Kazuhito Yoshikawa; Jun Sato; Akira Satoh; Aya Matsuda; Yoshimasa Kitagawa (MDPI AG, 2022)
Background: Carcinoma cuniculatum (CC) is a rare subtype of squamous cell carcinoma that is difficult to diagnose owing to the lack of cellar atypia and/or associated oral epithelial dysplasia. The prognosis is good given proper resection, but it often has a poor prognosis with recurrence. We present the case of a 78-year-old man who visited our department with an ulcer around the implant in tooth 35. With Nikolsky's phenomenon in the gingiva, a detailed examination revealed pemphigus vulgaris. Steroid administration remarkably improved the oral symptoms but caused osteomyelitis and rapid bone destruction, leading to pathological fracture. After multiple biopsies, mandibular segment resection was performed with a diagnosis of mandibular osteomyelitis, and no malignant findings were found. Four months later, the wound reopened, a white keratinized lesion appeared, and a biopsy revealed CC. Unresectable tumor infiltration was already observed, but the patient died of aspiration pneumonia 15 months after diagnosis. Conclusions: It took 20 months to make a definitive diagnosis of CC in this case. Pemphigus vulgaris may have made the diagnosis particularly difficult. Since other CCs are often diagnosed with osteomyelitis or odontogenic keratocyst preoperatively, we recommend keeping in mind the possibility of CC in refractory cases.